Record Broken: A Copper Peroxide Complex with Enhanced Stability and Faster Hydroxylation Catalysis. Issue 50 (13th June 2017) - Liebhäuser, Patricia; Keisers, Kristina; Hoffmann, Alexander; Schnappinger, Thomas; Sommer, Isabella; Thoma, Anne; Wilfer, Claudia; Schoch, Roland; Stührenberg, Kai; Bauer, Matthias; Dürr, Maximilian; Ivanović‐Burmazović, Ivana; et al.
Abstract: Tyrosinase model systems pinpoint pathways to translating Nature's synthetic abilities for useful synthetic catalysts. Mostly, they use N‐donor ligands which mimic the histidine residues coordinating the two copper centres. Copper complexes with bis(pyrazolyl)methanes with pyridinyl or imidazolyl moieties are already reported as excellent tyrosinase models. Substitution of the pyridinyl donor results in the new ligand HC(3‐ t BuPz)2 (4‐CO2 MePy) which stabilises a room‐temperature stable μ‐η 2 :η 2 ‐peroxide dicopper(II) species upon oxygenation. It reveals highly efficient catalytic activity as it hydroxylates 8‐hydroxyquinoline in high yields (TONs of up to 20) and much faster than all other model systems (max. conversion within 7.5 min). Stoichiometric reactions with para ‐substituted sodium phenolates show saturation kinetics which are nearly linear for electron‐rich substrates. The resulting Hammett correlation proves the electrophilic aromatic substitution mechanism. Furthermore, density functional theory (DFT) calculations elucidate the influence of the substituent at the pyridinyl donor: the carboxymethyl group adjusts the basicity and nucleophilicity without additional steric demand. This substitution opens up new pathways in reactivity tuning. Abstract : Trading places : This new tyrosinase model system exhibits a substituted pyridinyl moiety (drawn in red in the left structure) at the bis(pyrazolyl)methane ligand. Kinetic and catalytic studies with phenolic substrates and theoretical calculations display the influence of this ester substituent on stability and hydroxylation catalysis (see figure).